PENINGKATAN KESEJAHTERAAN MASYARAKAT DENGAN KUBE DI DESA KENDUNG SURABAYA - Yuli Ermawati; Suprayoga Suprayoga; Antoni Antoni (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Kendung village is known as "Kampung Semanggi" because the majority of semanggi traders both raw and processed semanggi come from this area. Starting from semanggi farmers, semanggi collectors, to traders of pecel semanggi and other semanggi preparations. The partners who become partners of the Community Empowerment Program (PPM) are 10 semanggi traders in Kendung RT 07 RW III. The conditions of their business activities have started to improve, some are still sitting in place, and some are experiencing a decline. The main problems faced by partners are the absence of well-organized business management and conventional external access to both funding and marketing and the absence of facilities that can facilitate them to form a community. The purpose of this empowerment is to explore the potential of semanggi traders in Kendung and find the right strategy to provide training, form a Joint Business Group among semanggi traders and escort them to get further empowerment from the government. The method used is mentoring 1) Making a SWOT analysis to explore the potential of clover traders in Kendung village, 2) For aspects of Business Management (Governance, finance, marketing), the Abmas team provides business management, finance, and online marketing training, 3) For Socio-Cultural aspects, the team inspires partners to form a Joint Business Group (KUBE) team and oversees proposals for submitting KUBE formation to sub-districts and reaches the relevant government offices to get further empowerment from the government. The results obtained are the implementation of training activities, the emergence of various variants of processed clover products, the formation of the "Omah Semanggi" Online Shop, and the formation of the KUBE "Smanggi Bersemi" to be continued to the relevant Government Service.